2023
DOI: 10.1109/access.2023.3249286
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Learners to Early Predict Their Performance in Educational Computer Games

Abstract: Data mining approaches have proven to be successful in improving learners´interaction with educational computer games. Despite the potential of predictive modelling in providing timely adaptive learning and gameplay experience, there is a lack of research on the early prediction of learners' performance in educational games. In this research, we propose an early predictive modelling approach, called GameEPM, to estimate learners' final scores in an educational game for promoting computational thinking. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…For instance, a solution that solely uses arrows to navigate the game, without the NPC catching the mouse, can still collect many Small_cheese features and accordingly achieve high scores. In educational games, a high score can be obtained through either a random strategy or an appropriate strategy, such as parallel thinking [82].…”
Section: Data Biasesmentioning
confidence: 99%
“…For instance, a solution that solely uses arrows to navigate the game, without the NPC catching the mouse, can still collect many Small_cheese features and accordingly achieve high scores. In educational games, a high score can be obtained through either a random strategy or an appropriate strategy, such as parallel thinking [82].…”
Section: Data Biasesmentioning
confidence: 99%
“…al. in Kuripan, Kertoharjo Village, showed that 17 the Tic Tac Toe game (Hooshyar et al, 2023). Based on research by Farida & Rini, 2013 the game Tic Tac Toe in the field of mathematics can increase learning motivation in cycle I by 83.88% and by 85.85% for cycle II.…”
Section: Introductionmentioning
confidence: 97%